INTERACTIVITY AS AN ESSENTIAL CHARACTERISTIC OF A POLYCULTURAL EDUCATION - Khadzhiev, Saydkhasan; Njudjurmagomedov, Abdulahad (Revista Inclusiones, 2020)
The relevance of the research is conditioned by the fact that the matter of human adaptation to conditions of polycultural social environment has not found a conclusive explanation in the known investigations so far. The paper shows that there are discrepancies in the viewpoints of globalists, ethnocentrists, followers of a person’s self-actualization and evolutionists. In this respect the present paper aims at comparative analysis of different theories and experience of polycultural education and development of its essential characteristics from the interactive point of development. The lead approach to the research of the matter is the use of interactive concept of education development, which enabled to consider the role of the ethnic culture, inner culture of a person and intercultural dialogue in polycultural education of the youth in an integrated manner. The specific characteristics of interactivity in a polycultural education, and author’s concept of interaction of the inner culture of a person and cultural differences as a driving force of apolycultural dialogue are specified, and ten dynamic stages of polycultural education implementation in the interactive concept of development are substantiated in the paper. The materials of the paper represent practical value for the teachers of educational institutions in arrangement of a polycultural education of the youth. The use of the proposed concept in educational activity significantly enhances the efficiency of the youth adaptation to communication in a polycultural environment.